Towards the synthesis of liposome for peptide embedding via microfluidic processes - Ng, Wei Quan (2015)
Present day, the Liposomes are a new form of drug delivery, as it is able to incorporate many functional materials in its core and transport it around. Because of the Multifunctional properties that Liposome possess, many studies have been done to create methods which are able to both make and load this Liposomes.One such method is Microfluidics, it is able to collect functional materials, while the intermediate lipid structure is growing, and incorporate this materials in the lipid core before the liposomes are fully formed. This project has nominated one flow condition, which has successfully reproduced liposomes of similar sizes (narrow distribution) and are large enough to allow peptide embedding. Before the commencement of any synthesis experiments, this project has tested and validated the functionality of a microfluidic device, which was the product from the collaboration with the National NanoFabrication Centre, Korea (NNFC). Using this microfluidic platform, liposomes from various flow conditions were synthesized. Without using any imaging techniques such SEM or TEM, real time visualized of the liposome were captured. This was made possible using Nanosight Tracking Analysis (NTA).Size distributions of liposomes were collected using both the NTA and Dynamic Light Scattering (DLS) Machines. The project onclusion was made based on the results. This project nominates (120:3) FRR40 as the ideal condition to synthesize the liposomes. The mean liposome size was 188 nm, and the condition consistently reproduced narrow size distribution, making it idea for peptide embedding applications. As an future recommendation, the project would like to recommend peptide embedding studies using this flow condtion,to find out the peptide entrapment efficiency. The results will be able endorse whether Microfluidics processes are capable being the best method to produce the multifunctional liposomes.